As contações de histórias problematizadoras no ensino de astronomia no 2° ano do ensino fundamental: entrelaçando fantasia e conhecimentos - Deus, Mariana Ferreira de (2013)
This study discusses the prior knowledge that second grade of Elementary School students have about the sun s and moon s apparent motion. Therefore, storytelling with Histórias Problematizadoras (HP\'s) were used, which consists of a methodological resource, developed by us, based on theoretical assumptions of Investigating Education, whose characteristic is the student\'s active participation in the learning process. The HP\'s are fictional texts with open endings, ended by a question, leading the students to unravel the problems posed related sometimes to the Sun, sometimes to the Moon. During the storytelling the children are given a moment to raise and discuss hypotheses about the subject, in addition we used as a resource the observation of the external environment to solve the problem-story introduced, in this case the sky above the school in the city of Uberlândia in which the research took place. 37 students of the second grade of elementary school participated in these activities and contributed to this study. The proposed aims were: to assess the potential of HP s as an educational resource for astronomy teaching and learning, and to check if the external environment observation, specifically the sky, is present in the children s everyday life. For this, we seek to answer the following question: which knowledge on students of 2nd grade of elementary school about apparent Sun and Moon motion are modified by participating in HP storytelling involving such issues. We worked with the stories \"A borboletinha de outro mundo\" (The little butterfly from another world), which deals with the Sun, and \"Lico e suas descobertas sobre Dona Lua\" (Lico and his discoveries about Miss Moon), which tells about the Moon. We had as reference to analyze the scientific production area about the students\' knowledge on the subject and curriculum proposals of teaching modality in question. The survey data were obtained from storytelling carried out by interviews and students discourses on the drawings they produced. Among the revealed students knowledge at the beginning of this research, we can mention: they didn t only observe natural objects of the astronomical sky, but also objects of biological natures, atmospheric, artificial and fantastic; using explanations from the religious point of view; designate the Sun from terms like circle, sphere, round ball; they explained the movement of the Sun and Moon from external elements, and use comparative terms to describe the moon shape. When analyzed by structure of thematic axes, students\' knowledge revealed during the research showed that they seek to explain the phenomena that occur daily from their experiences and not the change scientifically consolidated knowledge, but expand their ways of understanding the issues involved. Thus, in the end of the study, the majority of children now realize that: Sun changes its position along the hours, the Moon presents different aspects and can be seen both during the day and during the night, and describes a movement in the sky. In the case of HP\'s, we realized that they bring a playful way of approaching astronomical theme and reveals a possibility of active involvement learner in the learning process.